Fault Ride-Through Enhancement of Grid Supporting Inverter-Based Microgrid Using Delayed Signal Cancellation Algorithm Secondary Control - Elutunji Buraimoh; Innocent E. Davidson; Fernando Martinez-Rodrigo (Energies, 2019)
The growing level of grid-connected renewable energy sources in the form of microgrids has made it highly imperative for grid-connected microgrids to contribute to the overall system stability. Consequently, secondary services which include the fault ride-through (FRT) capability are expected to be possessed characteristics by inverter-based microgrids. This enhances the stable operation of the main grid and sustained microgrid grid interconnection during grid faults in conformity with the emerging national grid codes. This paper proposes an effective FRT secondary control strategy to coordinate power injection during balanced and unbalanced fault conditions. This complements the primary control to form a two-layer hierarchical control structure in the microgrids. The primary level is comprised of voltage/power and current inner loops fed by a droop control. The droop control coordinates grid power-sharing amongst the voltage source inverters. When a fault occurs, the participating inverters operate to support the grid voltage, by injecting supplementary reactive power based on their droop gains. Similarly, under unbalanced voltage condition due to asymmetrical faults in the grid, the proposed secondary control ensures the positive sequence component compensation and negative and zero sequence components clearance using a delayed signal cancellation (DSC) algorithm and power electronic switched series impedance placed in-between the point of common coupling (PCC) and the main grid. While ensuring that FRT ancillary service is rendered to the main utility, the strategy proposed ensures relatively interrupted quality power is supplied to the microgrid load. Consequently, this strategy ensures the microgrid ride-through the voltage sag and supports the grid utility voltage during the period of the main utility grid fault. Results of the study are presented and discussed.